Analysis of the daily consumption of potable water in the urban area of the Ambato city in the Province of Tungurahua-Ecuador. Issue 1 (December 2021) - Mayacela, M; Moya, D; Morales, F; Maldonado, L
Abstract: The consumption of drinking water has increased over the years worldwide, therefore, the analysis of daily consumption in a certain sector is important, to know the existing demand of the population of the sector under analysis. The study of water consumption not only allows the knowledge of the amount of water consumed in a population, it also enables future projects for the design and redesign of potable water distribution networks. The main methodology for this analysis was the daily record for a period of 60 days, in each of the sectors corresponding to the urban area of Ambato city; this methodology allowed the analysis of the typical week of the sector and therefore the amount of water consumed per day in the urban sector, it was concluded that the San Francisco parish presents the highest demand for water consumption per capita with a requirement of 256.48 L/inhab/day, the predominant type of residence in the urban area of the city of Ambato is type B, which is characterized by having a typical structural system in which reinforced concrete predominates.